Bonding situation in Be[N(SiMe3)2]2 – an experimental and computational study1. Issue 18 (4th March 2015) - Naglav, D.; Neumann, A.; Bläser, D.; Wölper, C.; Haack, R.; Jansen, G.; Schulz, S.
<x xml:space="preserve">Abstract</x> The solid state structure of Be[N(SiMe3)2]2 (1) was determined by in situ crystallisation and the bonding situation investigated by quantum chemical calculations. The Be–N bond is predominantly ionic but also shows some π-bonding character.